Unconventional diagnostic tests for Lyme borreliosis: a systematic review. (January 2020) - Raffetin, A.; Saunier, A.; Bouiller, K.; Caraux-Paz, P.; Eldin, C.; Gallien, S.; Jouenne, R.; Belkacem, A.; Salomon, J.; Patey, O.; Talagrand-Reboul, E.; Jaulhac, B.; et al.
Abstract: Background: Lyme borreliosis (LB) diagnosis currently relies mainly on serological tests and sometimes PCR or culture. However, other biological assays are being developed to try to improve Borrelia -infection diagnosis and/or monitoring. Objectives: To analyse available data on these unconventional LB diagnostic assays through a systematic literature review. Methods: We searched PubMed and Cochrane Library databases according to the PRISMA-DTA method and the Cochrane Handbook for Systematic Reviews of Interventions. We analysed controlled and uncontrolled studies (published 1983–2018) on biological tests for adults to diagnose LB according to the European Study Group for Lyme Borreliosis or the Infectious Diseases Society of America definitions, or identify strongly suspected LB. Two independent readers evaluated study eligibility and extracted data from relevant study reports; a third reader analysed full texts of papers to resolve disagreements. The quality of each included study was assessed with the QUADAS-2 evaluation scale. Results: Forty studies were included: two meta-analyses, 25 prospective controlled studies, five prospective uncontrolled studies, six retrospective controlled studies and two case reports. These biological tests assessed can be classified as: (i) proven to be effective at diagnosing LB and already in use (CXCL-13 for neuroborreliosis), but not enough to be standardized; (ii) not yet used routinely, requiring further clinical evaluation (CCL-19, OspA and interferon-α); (iii) uncertain LB diagnostic efficacy because of controversial results and/or poor methodological quality of studies evaluating them (lymphocyte transformation test, interferon-γ, ELISPOT); (iv) unacceptably low sensitivity and/or specificity (CD57 + natural killer cells and rapid diagnostic tests); and (v) possible only for research purposes (microscopy and xenodiagnoses). Discussion: QUADAS-2 quality assessment demonstrated high risk of bias in 25/40 studies and uncertainty regarding applicability for 32/40, showing that in addition to PCR and serology, several other LB diagnostic assays have been developed but their sensitivities and specificities are heterogeneous and/or under-evaluated or unassessed. More studies are warranted to evaluate their performance parameters. The development of active infection biomarkers would greatly advance LB diagnosis and monitoring.